Epidemiology, clinical manifestation, diagnosis,and treatment of bursitis iliopectinea: A systematic review - Malgorzata Lea Jonczy; Lorenz Büchler; Yadusha Mahenthiran; Fabrice Helfenstein; Christian Apenzeller-Herzog; Andrej Isaak (SAGE Open Medicine)
Background: Bursitis iliopectinea (BI) is a condition that is characterized by swelling of the iliopsoas bursa, leading to compression of inguinal neurovascular structures, causing swelling, pain, paresthesia, or thrombosis of the leg. Questions: Due to the rare occurrence of BI, the available literature consists of case reports. Our study aims to systematically review the literature for a comprehensive analysis of the etiology, treatment modalities, and clinical outcomes of patients with BI. Methods: We systematically analyzed 217 studies with 502 cases of BI and extracted information about the terminology, risk factors, diagnostic and treatment strategies, association with neurovascular compression syndromes, treatment outcomes, and recurrence rates. Results: The overall quality of the analyzed studies was moderate to good. The terminology uses for BI was heterogeneous and included ganglion, tumor, mass, and bursitis. In addition to conventional X-ray, ultrasound, CT, or MRI were used to diagnose BI. The most prevalent etiology of BI was osteoarthritis of the hip or wear-related soft-tissue reactions after total hip replacement (THA). Nearly one-third of the patients suffered from compression syndromes, most frequently of the femoral vein (16%). Only rheumatoid arthritis showed an association with the occurrence of compression syndromes. The most common operative treatments were the resection of the bursa (30%), total hip arthroplasty (29%), and aspiration (24%). Use of analgesics (17%), injection of corticoids (11%), and physiotherapy (9%) were used for conservative treatments. The recurrence rate was highest after physiotherapy (OR: 4.1) or aspiration (4.5) and lowest after THA (OR: 0.2). Conclusions: Although BI is a condition commonly associated with hip arthritis or local tissue reactions following total hip prosthesis, its impact extends beyond typical hip-related symptoms. Notably, BI related to rheumatoid arthritis shows a high correlation with neurovascular compression symptoms, with femoral vein compression being the most frequently reported. This underscores the necessity of considering BI in patients presenting with nonspecific inguinal pain or neurovascular symptoms of the lower extremity. Additionally, standardizing the nomenclature of BI nomenclature could improve future research.